Die problematiek van armoede met verwysing na onderwys, gesondheid en die gesin - Barnard, M. C. (Koers, 1995)
The problematic nature of poverty with reference to education, health and the family. Poverty is on the increase worldwide and goes hand in hand with unemployment. In South Africa poverty is inextricably interwoven with the historical and sociocultural legacy of the largest part of the population. The causes of poverty are extremely complex and must be sought in a combination of human and structural factors. Poverty has far-reaching influence on education, health and the family life of society. The question may be posed as to whether education has a decisive effect on the combating of poverty as such. In spite of the fact that education of a high standard is an important determinant in promoting literacy on an individual level, to improve quality of life and to develop human potential, it does not offer ready-made solutions for structural and cultural historical inequality and, this is nowhere more dearly reflected than in education. If education proposes to make a meaningful contribution to the combating of poverty, strategies such as more effective education financing, the partial privatisation o f education, greater utilisation of natural and human resources, the promotion of job creation and entrepreneurship, as well as enrichment of family life must be effected.